Decisions to Use Go-Food Services: Cultural, Social, Personal, and Psychological - Tumini, Tumini (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
The aim of this research is to examine the important role of several factors in determining the decision to use Go-Food services. The factors tested include cultural, social, personal and psychological factors. This research was conducted in Mayangan District, Probolinggo City. The method used a quantitative approach and the help of SPSS analysis tools. The research results show that cultural, social and personal factors do not influence a person's decision to use Jada Go-Food. Meanwhile, psychological factors have an influence on a person's decision to use Go-Food services. Research findings show that in the context of Mayangan District, Probolinggo City, cultural, social and personal factors do not play an important role in deciding to use Go-Food services, while psychological factors are considered to play an important role. The implication is that Go-Food service providers and marketers can focus more on marketing strategies that emphasize psychological aspects in an effort to increase adoption and decisions to use Go-Food services in the region.